2022
DOI: 10.1111/liv.15479
|View full text |Cite
|
Sign up to set email alerts
|

LINC01608 activated by YY1 facilitate hepatocellular carcinoma progression by modulating the EGFR/ERK axis

Abstract: Background: Long non-coding RNAs (LncRNAs) have been demonstrated to associate with a variety of cancers. However, the mechanisms of LncRNAs in hepatocellular carcinoma (HCC) progression are still not fully clarified.Methods: LINC01608 expression level in HCC and adjacent normal tissues was detected by real-time-quantitively PCR (RT-qPCR) in clinical samples and in situ hybridization (ISH) in tissue microarray. Several functional assays were performed to determine the biological effects of LINC01608 in HCC cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This allows the detachment of cells from the primary tumor and the separation of surrounding tissues and distant organs (41). Recent studies have shown that miR-875-5p plays an important role in influencing the EMT behavior of cancer cells (22,42). In vitro experiments revealed that inhibition of miR−875−5p promotes tumor growth and metastasis by promoting HCC cell epithelial−to−mesenchymal transition progression (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the detachment of cells from the primary tumor and the separation of surrounding tissues and distant organs (41). Recent studies have shown that miR-875-5p plays an important role in influencing the EMT behavior of cancer cells (22,42). In vitro experiments revealed that inhibition of miR−875−5p promotes tumor growth and metastasis by promoting HCC cell epithelial−to−mesenchymal transition progression (22).…”
Section: Discussionmentioning
confidence: 99%
“…An important finding is that overexpression of miR-875-5p promoted autophagy in CC cells, a novel mechanism by which miR-875-5p suppresses the growth of CC. To our knowledge, this is the first study exploring the correlation between miR-875-5p expression level and autophagy of CC cells, despite the involvement of miRs in other types of cancer (41)(42)(43)(44)(45)(46). Autophagy is a highly conserved catabolic process that plays a fundamental role in maintaining cellular homeostasis (43).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the signaling pathways mentioned above, other HS-binding growth factors can be modulated by SULFs as well. EGFR is the transmembrane receptor for various ligands including epidermal growth factor (EGF), heparinbinding EGF (HB-EGF), transforming growth factor α (TGF-α) and amphiregulin (AR) [80]. SULF1-mediated desulfation of cell surface HSPGs has been implicated in the reduction of EGFR phosphorylation, leading to the inhibition of tumor metastasis [81,82].…”
Section: Other Hs-binding Gfs Signaling Pathwaysmentioning
confidence: 99%